THE LATE BRONZE AGE GÁVA POTTERY FROM THE LOWER MUREȘ - Victor Sava; Adrian Ursuțiu (Journal of Ancient History and Archaeology)
The widespread societal collapse that occurred in the Lower Mureș Basin in the Late Bronze Age following the destruction of mega-sites during the 13th century BC is largely mirrored in the dwindling number of settlements, prestige goods, and metal finds. The same period is also associated with the spread of Gáva pottery. Apparently, the respective pottery style has been subject to thorough investigation; however, ceramic analyses and 14C data are quite scarce. We are publishing here a pottery assemblage from contexts located in the Lower Mureș Basin, where Gáva pottery style was discovered. Besides illustrating representative potsherds, we have analyzed their style and added 14C data when available. The results of the study proper and comparative analyses with other assemblages suggest a different perspective from certain approaches to Gáva culture as a unitary phenomenon. Starting from the stylistic features of the pottery, we have attempted at offering a regional perspective without overlooking the distinctive characteristics of a much wider area. Moreover, 14C data and previous studies on LBA II pottery enable us to argue that several well-known features of the Gáva pottery style can be identified, at least in the Lower Mureș Basin, as early as the 14th-13th century BC and even earlier, with some dating back to the 15th century BC.